Modelling Asparagopsis nitrogen bioremediation efficiency in Australian coastal environments - Tormey Reimer; Katherine A. Cresswell; Kate M. Fraser; Camille A. White; Scott A. Hadley (Ecological Modelling, 2026)

Watershed Continuum Monitoring Approach: combining multiple water quality patterns along stream and river flowpaths to track sources, pathways, and processing of pollutants - Sujay S. Kaushal; Ashley E. Mon; Stanley B. Grant; Paul M. Mayer; Aaron J. Porter; Andrew J. Sekellick; Jason H. Chase; Shantanu V. Bhide; John D. Jastram; Tamara A. Newcomer-Johnson; Sydney A. Shelton; Alexis M. Yaculak; et al. (Ecological Engineering, 2026)

Notes on the Utilization of Soft Corals by Fishes in Shallow Soft Coral-Dominated Reefs of Okinawa Island, Japan - Jue Alef A. Lalas; Rickdane Gomez; Takashi Nakamura; James Davis Reimer (Thalassas: An International Journal of Marine Sciences, 2026)

Methanobrevibacter smithii induces postnatal growth retardation through blunting hepatic ketone body metabolism - Ming Qi; Tongxing Song; Yuankun Deng; Na Li; Nan Wang; Andong Zha; Qing Ye; Chengming Wang; Yirui Shao; Yucheng Zhu; Ming Sun; Jens Walter; et al. (Science Bulletin, 2026)

Mellow Yellow: Exploring yellow soft coral dominance at Ama Beach, Kerama Shotō National Park, southern Japan - Fabian Gösser; Agus Alim Hakim; Jue Alef A. Lalas; Mattia Clavenna; Maria Paz Medina Monroy; Ulla von Ammon; Rickdane Gomez; James Davis Reimer (Regional Studies in Marine Science, 2025)

Gut microbiome-targeted therapies and bone health across the lifespan: a scoping review - Maahika Mehta; Erin Hodgson; Raylene A. Reimer; Leigh Gabel (Critical Reviews in Food Science and Nutrition, 2025)

Spawning and early-life history of the soft coral Sarcophyton cf. elegans (Octocorallia) in Okinawa Island, Japan, with notes on spawn predation by copepods - Agus A. Hakim; Emmeline A. Jamodiong; Geminne G. Manzano; Tracy D. Tabalanza; Sota Komeda; Daisuke Uyeno; Takashi Nakamura; Marin Anraku; Michihiro Kumekawa; Haruko Kurihara; James D. Reimer (Marine Biodiversity, 2025)

Microhabitat associations and benthic community structure of Nanipora (Helioporidae) across the western Pacific - Guillermo M. Castelló; Dan Ishibashi; Jue Alef A. Lalas; Iori Mizukami; Mackenzie L. B. Stoeltje; Meng C. Li; Hsiang-Lun Huang; Keryea Soong; James Davis Reimer (Marine Biodiversity, 2025)

Lunar cycle effects on pelagic predators and fisheries: insights into tuna, billfish, sharks, and rays - Samantha Andrzejaczek; Alexandra E. DiGiacomo; Chloe S. Mikles; Camille M. L. S. Pagniello; Theodore E. J. Reimer; Barbara A. Block (Reviews in Fish Biology and Fisheries, 2025)

Assessment of marine litter interactions with urban coral reefs in Okinawa, Japan - Ifenna Ilechukwu; Rocktim Ramen Das; Jue Alef Avanzado Lalas; Emmeline A. Jamodiong; Anže Abram; Stéphane De Palmas; James Davis Reimer (Marine Pollution Bulletin, 2024)

Patterns of fish assemblage structure on reefs with varying degrees of hard coral and soft coral dominance in Okinawa Island, Japan - Jue Alef A. Lalas; Rickdane Gomez; Anže Abram; Agus A. Hakim; Takashi Nakamura; James Davis Reimer (Marine Biodiversity, 2024)

Exposure to residential greenness, perceived stress, and depressive symptoms in a North American preconception cohort - Cameron J. Reimer; Mary D. Willis; Amelia K. Wesselink; Perry Hystad; Erin J. Campbell; Elizabeth E. Hatch; Kipruto Kirwa; Jaimie L. Gradus; Marco Vinceti; Lauren A. Wise; Marcia Pescador Jimenez (Environmental Research, 2024)

In situ observation of external surface brooding by Clavularia cf. inflata (Octocorallia) on reefs of northwestern Okinawa Island, Japan - Emmeline A. Jamodiong; Jue Alef A. Lalas; James D. Reimer (Invertebrate Reproduction & Development, 2024)

The Fourth Global Coral Bleaching Event: Where do we go from here? - James Davis Reimer; Raquel S. Peixoto; Sarah W. Davies; Nikki Traylor-Knowles; Morgan L. Short; Rafael A. Cabral-Tena; John A. Burt; Igor Pessoa; Anastazia T. Banaszak; R. Scott Winters; Tom Moore; Verena Schoepf; et al. (Coral Reefs, 2024)

Spatial patterns of soft coral (Octocorallia) assemblages in the shallow coral reefs of Okinawa Island, Ryukyu Archipelago, Japan: Dominance on highly disturbed reefs - Jue Alef A. Lalas; Emmeline A. Jamodiong; James D. Reimer (Regional Studies in Marine Science, 2024)

The British Columbia Farmers’ Market Nutrition Coupon Program Reduces Short-Term Household Food Insecurity Among Adults With Low Incomes: A Pragmatic Randomized Controlled Trial - Michelle L. Aktary; Sharlette Dunn; Tolulope Sajobi; Heather O’Hara; Peter Leblanc; Gavin R. McCormack; Stephanie Caron-Roy; Yun Yun Lee; Raylene A. Reimer; Leia M. Minaker; Kim D. Raine; Jenny Godley; et al. (Journal of the Academy of Nutrition and Dietetics, 2024)

Spawn release of a Sclerophytum soft coral species in Okinawa Island, Japan - Emmeline A. Jamodiong; Tracy D. Tabalanza; Meangeldil A. Azuma-Malsol; Geminne G. Manzano; Agus A. Hakim; Takashi Nakamura; James D. Reimer (Marine Biodiversity, 2024)

Abundance and distribution of marine litter on the beaches of Okinawa Island, Japan - Ifenna Ilechukwu; Rocktim Ramen Das; Emmeline A. Jamodiong; Stefano Borghi; Geminne G. Manzano; Agus Alim Hakim; James Davis Reimer (Marine Pollution Bulletin, 2024)

Do contaminants compromise the use of recycled nutrients in organic agriculture? A review and synthesis of current knowledge on contaminant concentrations, fate in the environment and risk assessment - E.K. Bünemann; M. Reimer; E. Smolders; S.R. Smith; M. Bigalke; A. Palmqvist; K.K. Brandt; K. Möller; R. Harder; L. Hermann; B. Speiser; F. Oudshoorn; et al. (Science of The Total Environment, 2024)

Molecular phylogeny of the genus Dorometra Clark, 1917 (Crinoidea: Comatulida: Antedonidae): a new genus and new insights for future taxonomic revisions of Antedonidae - R. Virgili; A. Poliseno; T. Fujita; G. A. Pratama; I. Fernández-Silva; J. D. Reimer (Systematics and Biodiversity, 2023)

Distribution and molecular phylogeny of the octocoral genus Nanipora (Helioporidae) in the western Pacific - Guillermo Mironenko Castelló; Emmeline A. Jamodiong; Jue Alef Avanzado Lalas; Rahul Mehrotra; James Davis Reimer (Marine Biodiversity, 2023)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

Coral assemblages at higher latitudes favor short‐term potential over long‐term performance - James Cant; James D. Reimer; Brigitte Sommer; Katie M. Cook; Sun W. Kim; Carrie A. Sims; Takuma Mezaki; Cliodhna O'Flaherty; Maxime Brooks; Hamish A. Malcolm; John M. Pandolfi; Roberto Salguero‐Gómez; et al. (Ecology, 2023)
The persistent exposure of coral assemblages to more variable abiotic regimes is assumed to augment their resilience to future climatic variability. Yet, while the determinants of coral population resilience across species remain unknown, we are unable to predict the winners and losers across reef ecosystems exposed to increasingly variable conditions. Using annual surveys of 3171 coral individuals across Australia and Japan (2016–2019), we explore spatial variation across the short‐ and long‐term dynamics of competitive, stress‐tolerant, and weedy assemblages to evaluate how abiotic variability mediates the structural composition of coral assemblages. We illustrate how, by promoting short‐term potential over long‐term performance, coral assemblages can reduce their vulnerability to stochastic environments. However, compared to stress‐tolerant, and weedy assemblages, competitive coral taxa display a reduced capacity for elevating their short‐term potential. Accordingly, future climatic shifts threaten the structural complexity of coral assemblages in variable environments, emulating the degradation expected across global tropical reefs.

High abundances of zooxanthellate zoantharians (Palythoa and Zoanthus) at multiple natural analogues: potential model anthozoans? - James Davis Reimer; Sylvain Agostini; Yimnang Golbuu; Ben P. Harvey; Michael Izumiyama; Emmeline A. Jamodiong; Erina Kawai; Hajime Kayanne; Haruko Kurihara; Timothy Ravasi; Shigeki Wada; Riccardo Rodolfo-Metalpa (Coral Reefs, 2023)

Macroalgae exhibit diverse responses to human disturbances on coral reefs - Sara E. Cannon; Simon D. Donner; Angela Liu; Pedro C. González Espinosa; Andrew H. Baird; Julia K. Baum; Andrew G. Bauman; Maria Beger; Cassandra E. Benkwitt; Matthew J. Birt; Yannick Chancerelle; Joshua E. Cinner; et al. (Global Change Biology, 2023)
Scientists and managers rely on indicator taxa such as coral and macroalgal cover to evaluate the effects of human disturbance on coral reefs, often assuming a universally positive relationship between local human disturbance and macroalgae. Despite evidence that macroalgae respond to local stressors in diverse ways, there have been few efforts to evaluate relationships between specific macroalgae taxa and local human‐driven disturbance. Using genus‐level monitoring data from 1205 sites in the Indian and Pacific Oceans, we assess whether macroalgae percent cover correlates with local human disturbance while accounting for factors that could obscure or confound relationships. Assessing macroalgae at genus level revealed that no genera were positively correlated with all human disturbance metrics. Instead, we found relationships between the division or genera of algae and specific human disturbances that were not detectable when pooling taxa into a single functional category, which is common to many analyses. The convention to use percent cover of macroalgae as an indication of local human disturbance therefore likely obscures signatures of local anthropogenic threats to reefs. Our limited understanding of relationships between human disturbance, macroalgae taxa, and their responses to human disturbances impedes the ability to diagnose and respond appropriately to these threats.

Phylogenomics of Palythoa (Hexacorallia: Zoantharia): probing species boundaries in a globally distributed genus - ‘Ale‘alani Dudoit; Maria E. A. Santos; James D. Reimer; Robert J. Toonen (Coral Reefs, 2022)

An integrative approach reveals a new species of Zoantharia (Cnidaria, Anthozoa), Terrazoanthus silveirai , in the South-western Atlantic Ocean - Claudia F. Vaga; Alvaro E. Migotto; Maria E. A. Santos; Renato M. Honji; James Reimer; Marcelo V. Kitahara (Marine Biology Research, 2021)

Cliff Retreat Contribution to the Littoral Sediment Budget along the Baltic Sea Coastline of Schleswig-Holstein, Germany - Tanita Averes; Jacobus L. A. Hofstede; Arfst Hinrichsen; Hans-Christian Reimers; Christian Winter (Journal of Marine Science and Engineering, 2021)
Mobile coastal sediments, such as sand and gravel, build up and protect wave-dominated coastlines. In sediment-starved coastal environments, knowledge about the natural sources and transport pathways of those sediments is of utmost importance for the understanding and management of coastlines. Along the Baltic Sea coast of Schleswig-Holstein (Germany), the retreat of active cliffs—made of cohesive Pleistocene deposits—supplies a wide size range of sediments to the coastal system. The material is reworked and sorted by hydrodynamic forcing: the less mobile stones and boulders remain close to the source area; the finest sediments, mostly clay and silt, are transported offshore into areas of low energy; and the fractions of sand and fine gravels mostly remain in the nearshore zone, where they make up the littoral sediment budget. They contribute to the morphodynamic development of sandy coastlines and nearshore bar systems. Exemplarily for this coastal stretch and based on an extensive review of local studies we quantify the volume of the potential littoral sediment budget from cliff retreat. At an average retreat rate of 0.24 m yr−1 (

Global diversity and distribution of Lamippidae copepods symbiotic on Octocorallia - Oksana A. Korzhavina; James D. Reimer; Hermann Ehrlich; Viatcheslav N. Ivanenko (Symbiosis, 2021)

Low Static Shear Modulus Along Foliation and Its Influence on the Elastic and Strength Anisotropy of Poorman Schist Rocks, Homestake Mine, South Dakota - Katherine J. Condon; Hiroki Sone; Herbert F. Wang; J. Ajo-Franklin; T. Baumgartner; K. Beckers; D. Blankenship; A. Bonneville; L. Boyd; S. Brown; J. A. Burghardt; C. Chai; et al. (Rock Mechanics and Rock Engineering, 2020)

Acidification in the U.S. Southeast: Causes, Potential Consequences and the Role of the Southeast Ocean and Coastal Acidification Network - Emily R. Hall; Leslie Wickes; Louis E. Burnett; Geoffrey I. Scott; Debra Hernandez; Kimberly K. Yates; Leticia Barbero; Janet J. Reimer; Mohammed Baalousha; Jennifer Mintz; Wei-Jun Cai; J. Kevin Craig; et al. (Frontiers in Marine Science, 2020)

Octocoral-associated Parazoanthus cf. swiftii from the southwestern Atlantic - Claudia F. Vaga; Maria E. A. Santos; Alvaro E. Migotto; James Reimer; Marcelo V. Kitahara (Marine Biodiversity, 2020)

Modeling optimal responses and fitness consequences in a changing Arctic - Jody R. Reimer; Marc Mangel; Andrew E. Derocher; Mark A. Lewis (Global Change Biology, 2019)
Animals must balance a series of costs and benefits while trying to maximize their fitness. For example, an individual may need to choose how much energy to allocate to reproduction versus growth, or how much time to spend on vigilance versus foraging. Their decisions depend on complex interactions between environmental conditions, behavioral plasticity, reproductive biology, and energetic demands. As animals respond to novel environmental conditions caused by climate change, the optimal decisions may shift. Stochastic dynamic programming provides a flexible modeling framework with which to explore these trade‐offs, but this method has not yet been used to study possible changes in optimal trade‐offs caused by climate change. We created a stochastic dynamic programming model capturing trade‐off decisions required by an individual adult female polar bear ( Ursus maritimus ) as well as the fitness consequences of her decisions. We predicted optimal foraging decisions throughout her lifetime as well as the energetic thresholds below which it is optimal for her to abandon a reproductive attempt. To explore the effects of climate change, we shortened the spring feeding period by up to 3 weeks, which led to predictions of riskier foraging behavior and higher reproductive thresholds. The resulting changes in fitness may be interpreted as a best‐case scenario, where bears adapt instantaneously and optimally to new environmental conditions. If the spring feeding period was reduced by 1 week, her expected fitness declined by 15%, and if reduced by 3 weeks, expected fitness declined by 68%. This demonstrates an effective way to explore a species' optimal response to a changing landscape of costs and benefits and highlights the fact that small annual effects can result in large cumulative changes in expected lifetime fitness.

Exploring the Biodiversity of Understudied Benthic Taxa at Mesophotic and Deeper Depths: Examples From the Order Zoantharia (Anthozoa: Hexacorallia) - James Davis Reimer; Hiroki Kise; Maria E. A. Santos; Dhugal John Lindsay; Richard L. Pyle; Joshua M. Copus; Brian W. Bowen; Masanori Nonaka; Takuo Higashiji; Yehuda Benayahu (Frontiers in Marine Science, 2019)

Late Pleistocene glaciation in the Mosquito Range, Colorado, USA: chronology and climate - Keith A. Brugger; Benjamin Laabs; Alexander Reimers; Noah Bensen (Journal of Quaternary Science, 2019)
New cosmogenic 10 Be surface exposure ages from 17 moraine boulders in the Mosquito Range of Colorado suggest that glaciers were at their late Pleistocene (Pinedale) maximum extent at ∼21–20 ka, and that ice recession commenced before ∼17 ka. These age limits suggest that the Pinedale Glaciation was synchronous within the Colorado Rocky Mountain region. Locally, the previous (Bull Lake) glaciation appears to have occurred no later than 117 ka, possibly ∼130 ka allowing for reasonable rock weathering rates. Temperature‐index modeling is used to determine the magnitude of temperature depression required to maintain steady‐state mass balances of seven reconstructed glaciers at their maximum extent. Assuming no significant differences in precipitation compared to modern values, mean annual temperatures were ∼8.1 and 7.5 °C lower, respectively, on the eastern and western slopes of the range with quantifiable uncertainties of + 0.8/−0.9 °C. If an average temperature depression of 7.8 °C is assumed for the entire range, precipitation differences − that today are 15–30% greater on the eastern slope due to the influence of winter/early spring snowfall − might have been enhanced. The temperature depressions inferred here are consistent with similarly derived values elsewhere in the Colorado Rockies and those inferred from regional‐scale climate modeling.

Diversity of Saint Helena Island and zoogeography of zoantharians in the Atlantic Ocean: Jigsaw falling into place - Maria E. A. Santos; Peter Wirtz; Javier Montenegro; Hiroki Kise; Cataixa López; Judith Brown; James Davis Reimer (Systematics and Biodiversity, 2019)

Diet-induced obesity leads to pro-inflammatory alterations to the vitreous humour of the eye in a rat model - Kelsey H. Collins; Walter Herzog; Raylene A. Reimer; Carol R. Reno; Bryan J. Heard; David A. Hart (Inflammation Research, 2018)

Zooxanthellate zoantharians (Anthozoa: Hexacorallia: Zoantharia: Brachycnemina) in the northern Red Sea - James Davis Reimer; Javier Montenegro; Maria E. A. Santos; Martyn E. Y. Low; Marcela Herrera; Remy Gatins; May B. Roberts; Michael L. Berumen (Marine Biodiversity, 2017)

On the paraphyly of Cytaeididae and placement of Cytaeis within the suborder Filifera (Hydrozoa: Anthoathecata) - A. A. Prudkovsky; M. A. Nikitin; M. L. Berumen; Viatcheslav N. Ivanenko; J. D. Reimer (Marine Biodiversity, 2017)

Population genomics of the filarial nematode parasite Wuchereria bancrofti from mosquitoes - Scott T. Small; Lisa J. Reimer; Daniel J. Tisch; Christopher L. King; Bruce M. Christensen; Peter M. Siba; James W. Kazura; David Serre; Peter A. Zimmerman (Molecular Ecology, 2016)
Wuchereria bancrofti is a parasitic nematode and the primary cause of lymphatic filariasis – a disease specific to humans. W. bancrofti currently infects over 90 million people throughout the tropics and has been acknowledged by the world health organization as a vulnerable parasite. Current research has focused primarily on the clinical manifestations of disease and little is known about the evolutionary history of W. bancrofti . To improve upon knowledge of the evolutionary history of W. bancrofti , we whole genome sequenced 13 W. bancrofti larvae. We circumvent many of the difficulties of multiple infections by sampling larvae directly from mosquitoes that were experimentally inoculated with infected blood. To begin, we used whole genome data to reconstruct the historical population size. Our results support a history of fluctuating population sizes that can be correlated with human migration and fluctuating mosquito abundances. Next, we reconstructed the putative pedigree of W. bancrofti worms within an infection using the kinship coefficient. We deduced that there are full‐sib and half‐sib relationships residing within the same larval cohort. Through combined analysis of the mitochondrial and nuclear genomes we concluded that this is likely a results of polyandrous mating, the first time reported for W. bancrofti . Lastly, we scanned the genomes for signatures of natural selection. Annotation of putative selected regions identified proteins that may have aided in a parasitic life style or may have evolved to protect against current drug treatments. We discuss our results in the greater context of understanding the biology of an animal with a unique life history and ecology.

Yellow tails in the Red Sea: phylogeography of the Indo‐Pacific goatfish Mulloidichthys flavolineatus reveals isolation in peripheral provinces and cryptic evolutionary lineages - Iria Fernandez‐Silva; John E. Randall; Richard R. Coleman; Joseph D. DiBattista; Luiz A. Rocha; James D. Reimer; Carl G. Meyer; Brian W. Bowen (Journal of Biogeography, 2015)
Aim Broadly distributed reef fishes tend to have high gene flow mediated by a pelagic larval phase. Here, we survey a reef‐associated fish distributed across half the tropical oceans, from the Red Sea to the central Pacific. Our goal is to determine whether genetic structure of the broadly distributed Yellowstripe Goatfish ( Mulloidichthys flavolineatus ) is defined by biogeographical barriers, or facilitated via larval dispersal. Location Red Sea, Indian Ocean, Pacific Ocean Methods Specimens were obtained at 19 locations from the Red Sea to Hawai'i. Genetic data include mt DNA cytochrome b ( n = 217) and 12 microsatellite loci ( n = 185). Analysis of molecular variance ( AMOVA ), structure , a parsimony network and coalescence analyses were used to resolve recent population history and connectivity. Results Population structure was significant (mt DNA ϕ ST = 0.68, P 0.001; microsatellite F ST = 0.08, P 0.001), but mostly driven by samples from the North‐western ( NW ) Indian Ocean (including the Red Sea) and Hawai'i. There was little population structure across the Indian Ocean to the central Pacific. Hawai'i was distinguished as an isolated population (mt DNA ϕ ST = 0.03–0.08, P = n.s.; microsatellites F ST = 0.05–0.10, P 0.001). Specimens from the NW Indian Ocean clustered as a distinct phylogenetic lineage that diverged approximately 493 ka ( d = 1.7%), which indicates that these fish persisted in isolation through several Pleistocene glacial cycles. Main conclusions These data reinforce the emerging themes that: (1) phylogeographical breaks within species often coincide with biogeographical breaks based on species distributions, and (2) populations on the periphery of the range ( NW Indian Ocean and Hawai'i) are isolated and may be evolutionary incubators producing new species.

Whole‐genome sequencing reveals absence of recent gene flow and separate demographic histories for Anopheles punctulatus mosquitoes in Papua New Guinea - Kyle Logue; Scott T. Small; Ernest R. Chan; Lisa Reimer; Peter M. Siba; Peter A. Zimmerman; David Serre (Molecular Ecology, 2015)
Anopheles mosquitoes are the vectors of several human diseases including malaria. In many malaria endemic areas, several species of Anopheles coexist, sometimes in the form of related sibling species that are morphologically indistinguishable. Determining the size and organization of Anopheles populations, and possible ongoing gene flow among them is important for malaria control and, in particular, for monitoring the spread of insecticide resistance alleles. However, these parameters have been difficult to evaluate in most Anopheles species due to the paucity of genetic data available. Here, we assess the extent of contemporary gene flow and historical variations in population size by sequencing and de novo assembling the genomes of wild‐caught mosquitoes from four species of the Anopheles punctulatus group of Papua New Guinea. Our analysis of more than 50 Mb of orthologous DNA sequences revealed no evidence of contemporary gene flow among these mosquitoes. In addition, investigation of the demography of two of the An. punctulatus species revealed distinct population histories. Overall, our analyses suggest that, despite their similarities in morphology, behaviour and ecology, contemporary sympatric populations of An. punctulatus are evolving independently.

Molecular and morphological evidence for conspecificity of two common Indo-Pacific species of Palythoa (Cnidaria: Anthozoa) - Yuya Hibino; Peter A. Todd; Sung-yin Yang; Yehuda Benayahu; James Davis Reimer (Hydrobiologia, 2014)

Tubular Heart Valves from Decellularized Engineered Tissue - Zeeshan H. Syedain; Lee A. Meier; Jay M. Reimer; Robert T. Tranquillo (Annals of Biomedical Engineering, 2013)

Morphologically plastic responses to shading in the zoanthids Zoanthus sansibaricus and Palythoa tuberculosa - Chin Wei Ong; James D. Reimer; Peter A. Todd (Marine Biology, 2013)

Antineoplastic agent busulfan regulates a network of genes related to coagulation and fibrinolysis - Janka Reimer; Sandra Bien; Sabine Ameling; Elke Hammer; Uwe Völker; Georg Hempel; Joachim Boos; Heyo K. Kroemer; Christoph A. Ritter (European Journal of Clinical Pharmacology, 2012)

Coral-killing cyanobacteriosponge (Terpios hoshinota) on the Great Barrier Reef - T. Fujii; S. Keshavmurthy; W. Zhou; E. Hirose; C. A. Chen; J. D. Reimer (Coral Reefs, 2011)

New records and molecular characterization of Acrozoanthus (Cnidaria: Anthozoa: Hexacorallia) and its endosymbionts (Symbiodinium spp.) from Taiwan - James Davis Reimer; Sohta A. Ishikawa; Mamiko Hirose (Marine Biodiversity, 2011)

Legionella pneumophila monoclonal antibody subgroups and DNA sequence types isolated in Canada between 1981 and 2009: Laboratory Component of National Surveillance - A. R. Reimer; S. Au; S. Schindle; K. A. Bernard (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Allelic variation at Psy1-A1 and association with yellow pigment in durum wheat grain - A. Singh; S. Reimer; C. J. Pozniak; F. R. Clarke; J. M. Clarke; R. E. Knox; A. K. Singh (Theoretical and Applied Genetics, 2009)

Intratracheal Versus Intravenous Liposomal Delivery of siRNA, Antisense Oligonucleotides and Anticancer Drug - Olga B. Garbuzenko; Maha Saad; Seema Betigeri; Min Zhang; Alexandre A. Vetcher; Viatcheslav A. Soldatenkov; David C. Reimer; Vitaly P. Pozharov; Tamara Minko (Pharmaceutical Research, 2009)

Evolutionary origin of the segmental duplication encompassing the wheat GLU-B1 locus encoding the overexpressed Bx7 (Bx7OE) high molecular weight glutenin subunit - Raja Ragupathy; Hamid A. Naeem; Elsa Reimer; Odean M. Lukow; Harry D. Sapirstein; Sylvie Cloutier (Theoretical and Applied Genetics, 2008)

Evidence for subdivision within the M molecular form of Anopheles gambiae - M. A. SLOTMAN; F. TRIPET; A. J. CORNEL; C. R. MENESES; Y. LEE; L. J. REIMER; T. C. THIEMANN; E. FONDJO; A. FOFANA; S. F. TRAORÉ; G. C. LANZARO (Molecular Ecology, 2007)
The principal vector of malaria in sub‐Saharan Africa, Anopheles gambiae is subdivided into two molecular forms M and S. Additionally, several chromosomal forms, characterized by the presence of various inversion polymorphisms, have been described. The molecular forms M and S each contain several chromosomal forms, including the Savanna, Mopti and Forest forms. The M and S molecular forms are now considered to be the reproductive units within A. gambiae and it has recently been argued that a low recombination rate in the centromeric region of the X chromosome has facilitated isolation between these forms. The status of the chromosomal forms remains unclear however. Therefore, we studied genetic differentiation between Savanna S, Forest S, Forest M and Mopti M populations using microsatellites. Genetic differentiation between Savanna S and Forest S populations is very low ( F ST = 0.0053 ± 0.0049), even across large distances. In comparison, the Mopti M and Forest M populations show a relatively high degree of genetic differentiation ( F ST = 0.0406 ± 0.0054) indicating that the M molecular form may not be a single entity, but could be subdivided into at least two distinct chromosomal forms. Previously it was proposed that inversions have played a role in the origin of species within the A. gambiae complex. We argue that a possible subdivision within the M molecular form could be understood through this process, with the acquisition of inversions leading to the expansion of the M molecular form into new habitat, dividing it into two distinct chromosomal forms.

Two Species of Stephanostomum Looss, 1899 (Digenea: Acanthocolpidae) from Marine Fishes off Namibia, Including S. Beukelaardori n. sp. - Rodney A. Bray; Lothar W. Reimer (Systematic Parasitology, 2004)

Genotypic Characterization of an MHC Class II Locus in Lake Trout (Salvelinus namaycush) from Lake Superior by Single-Stranded Conformational Polymorphism Analysis and Reference Strand?Mediated Conformational Analysis - Marc A. Noakes; Tara Reimer; Ruth B. Phillips (Marine Biotechnology, 2003)

Carbon cycling in the German Bight: An estimate of transformation processes and transport - A. Reimer; S. Brasse; R. Doerffer; C. -D. Dürselen; S. Kempe; W. Michaelis; H. -J. Rick; R. Seifert (Ocean Dynamics, 1999)

SPM concentrations in the German Bight: comparison between a model simulation and measurements - W. Puls; J. Beusekom; U. Brockmann; R. Doerffer; U. Hentschke; P. König; D. Murphy; B. Mayer; A. Müller; Th. Pohlmann; A. Reimer; R. Schmidt-Nia; et al. (Ocean Dynamics, 1999)

Relative and combined effects of ethanol and protein deficiency on strontium and barium bone content and fecal and urinary excretion - E. Gonzalez-Reimers; F. Rodriguez-Moreno; A. Martinez-Riera; A. Mas-Pascual; E. Delgado-Ureta; L. Galindo-Martin; M. Arnay-de La Rosa; F. Santolaria-Fernandez (Biological Trace Element Research, 1999)

Chemical Ozone Loss in the Arctic Winter 1994/95 as Determined by the Match Technique - M. Rex; P. Von Der Gathen; G.O. Braathen; N.R.P. Harris; E. Reimer; A. Beck; R. Alfier; R. Krüger-carstensen; M. Chipperfield; H. De Backer; D. Balis; F. O'Connor; et al. (Journal of Atmospheric Chemistry, 1999)

A Study of Ozone Laminae Using Diabatic Trajectories, Contour Advection and Photochemical Trajectory Model Simulations. - S. J. Reid; M. Rex; P. Von Der Gathen; I. Fløisand; F. Stordal; G. D. Carver; A. Beck; E. Reimer; R. Krüger-Carstensen; L. L. De Haan; G. Braathen; V. Dorokhov; et al. (Journal of Atmospheric Chemistry, 1998)

An autonomous. bottom‐transecting vehicle for making long time‐series measurements of sediment community oxygen consumption to abyssal depths - K. L. Smith; R. C. Glatts; R. J. Baldwin; S. E. Beaulieu; A. H. Uhlman; R. C. Horn; C. E. Reimers (Limnology and Oceanography, 1997)
We have developed and successfully collected data with a unique, bottom‐transecting vehicle (ROVER) that permits the first long time‐series measurements of sediment community oxygen consumption (SCOC). This instrument has the following capabilities: (1) it operates as an autonomous, free vehicle on the sea floor to 6,000‐m depth for periods up to 6 months; (2) it transits across the sea floor, minimizing the impact that a long‐term, free‐vehicle structure would have on measurement sites; (3) it measures SCOC by using duplicate benthic chambers at up to 30 different sites over a single deployment period; (4) it measures sediment porewater oxygen concentration as an independent measure of SCOC by using a microprofiler at up to 30 different sites over a single deployment period; (5) it has an incubation period of programmable duration for each SCOC measurement; (6) it monitors operation of instruments and the surrounding area with time‐lapse still and video cameras; (7) it has the flexibility to be used as an autonomous programmable platform for a wide variety of benthic boundary‐layer measurements; and (8) it collects a water sample for oxygen and other analyses at the end of the deployment. The ROVER resembles a small forklift with a forward‐mounted instrument assembly, a current meter, double‐tread propulsion system, central battery and controller electronics, flotation, acoustic releases, and disposable ballast. The ROVER was deployed for a 4‐month period (January–May 1996) to measure SCOC at 4,100‐m depth in the eastern North Pacific. During this deployment the ROVER occupied 17 sites with each benthic chamber incubation lasting 152.3 h and a 17‐h interval between incubations for repositioning and transit. SCOC ranged from 0.50 to 0.91 mmol O 2 n −2 d −1 , generally declining from January until the end of February and then increasing irregularly to the end of the deployment in late May. These measurements show good agreement with those made at the same site with another autonomous instrument, the free‐vehicle grab respirometer, at the beginning and end of the ROVER deployment.

Application of a solid-phase immunofluorometric assay to the selection of monoclonal antibody specific for the adenovirus group-reactive hexon antigen - J. C. Hierholzer; D. J. Phillips; D. D. Humphrey; R. A. Coombs; C. B. Reimer (Archives of Virology, 1984)